Calibration of RADMON radiation monitor onboard Aalto-1 CubeSat - Oleynik P; Vainio R; Punkkinen A; Dudnik O; Gieseler J; Hedman H; Hietala H; Hæggström E; Niemelä P; Peltonen J; Praks J; Punkkinen R; et al. (Elsevier Ltd, 2022)
RADMON is a small radiation monitor designed and assembled by students of University of Turku and University of Helsinki. It is flown on-board Aalto-1, a 3-unit CubeSat in low Earth orbit at about 500 km altitude. The detector unit of the instrument consists of two detectors, a Si solid-state detector and a CsI(Tl) scintillator, and utilizes the ΔE-E technique to determine the total energy and species of each particle hitting the detector. We present the results of the on-ground and in-flight calibration campaigns of the instrument, as well as the characterization of its response through extensive simulations within the Geant4 framework. The overall energy calibration margin achieved is about 5%. The full instrument response to protons and electrons is presented and the issue of proton contamination of the electron channels is quantified and discussed.